Greenness, blueness and whiteness evaluated rapid Attenuated Total Reflection/ Fourier Transform Infrared Spectroscopy method for piper nigrum Samples Coupled with multivariate analysis - Rinkal N Patel; Kunjal L Vegad; Ruchik V Mistry; Nikunj D Patel (Green Analytical Chemistry)
“Piper nigrum”, a very well-known black gold is recommended to treat numerous ailments. The primary concerns in quality of piper nigrum arise due to numerous factors including adulteration, omission and partial substitution. A novel, rapid, steadfast method based on attenuated total reflectance - Fourier transform infrared (ATR-FTIR) technique with a diamond crystal was developed to evaluate samples of piper nigrum. Total twenty-six different samples including authenticated in-house sample were studied. For, Fourier transform infrared study transmittance mode was kept to record the spectra. The resultant data was then treated with chemometric method. Chemometric methods like Principal Component Analysis was used for quality assessment of piper nigrum by evaluating the differences in market samples. 25 important FTIR peaks responsible for complete variation for routine analysis of piper nigrum samples were identified and based on score plot of Principal Component Analysis (PCA), outliers were distinguished from the authenticated piper nigrum sample. The greenness, evaluation of the developed method was achieved through Complementary Green Analytical Procedure Index (Complex GAPI) (85), Analytical Greenness Metric (AGREE) (0.95) revealing the method's favourable eco-friendly profile. Blueness evaluation through Blue Applicability Grade Index (BAGI) score (80) indicated excellent applicability, while whiteness evaluation through the precise re-versioned RGB pretty good score (Ex ante: 91.8, Ex post: 91.4) confirmed cost-effectiveness and sustainability. This novel eco-friendly approach offers a rapid, green, blue and-white substitute to available conventional analytical techniques. The developed method was easy to handle, cheaper, simple, rapid, precise and stable that can be used as an effective routine quality assessment of piper nigrum.